Implications of Clay Minerals in Landslide Disasters: Case Study of the Riau - West Sumatra Highway KM 82 - 89 - Suryadi, Adi; Wuldan, Muhammad; Kausarian, Husnul (Journal of Applied Geospatial Information, 2024)
The research area is along the Riau - West Sumater highway KM 82 - 89 where landslides are very common. The factors most often discussed are rainfall intensity, degree of slope, geological structure and the presence of plants. In this research, the factor of the presence of clay is the main focus in its influence on the occurrence of landslides. Landslide sampling is carried out at landslide locations. Soil samples were also carried out in laboratory simulations of the process of landslides. The methods used to identify the type of clay are Scanning Electron Microscope (SEM) and X-ray diffraction analysis (XRD). The results of the analysis showed that all of the 3 soil samples analyzed using SEM showed the presence of Kaolinite, Montmorillonite and Illite types of clay. In terms of the percentage of clay presence based on XRD analysis at 3 stations, it shows the presence of Kaolinite clay in each soil sample with the percentage of ST1, ST2 and ST3 Kaolinite presence are 29.55%, 18.33% and 36.67%. The presence of Montmorillonite and Illite is indicated by the presence of the mineral Muscovite from the SEM analysis results where its presence is only found in ST1 and ST2 with percentages of 34.85% and 26.67%. The implication of the presence of Montmorillonite and Illite clay is an important factor in the occurrence of landslides, especially the size of the landslide that occurs. This is shown by the linearity between the percentage of Montmorillonite and Illite presence and the distance of the landslide that occurred in the simulation results.